2003
DOI: 10.1046/j.1529-8817.2003.02120.x
|View full text |Cite
|
Sign up to set email alerts
|

SOME PRYMNESIACEAE (HAPTOPHYTA, PRYMNESIOPHYCEAE) FROM THE MEDITERRANEAN SEA, WITH THE DESCRIPTION OF TWO NEW SPECIES:CHRYSOCHROMULINA LANCEOLATASP. NOV. ANDC. PSEUDOLANCEOLATASP. NOV.1

Abstract: Five species belonging to the family Prymnesiaceae (one Prymnesium and four Chrysochromulina) have been identified in cultures obtained from water collected in the Bay of Banyuls‐sur‐Mer (Mediterranean Sea, France) using LM, SEM, and TEM. Two are described as new species, Chrysochromulina lanceolata sp. nov. and C. pseudolanceolata sp. nov. Both species are large and lanceolate with an acute posterior and two anterior arms. They are easily detectable with LM but difficult to distinguish to species level with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The center of the scales has a cruciform structure surrounded by an open ring with radiate ribs extending out of the central ring to the rim and crossed by spiraling ribs. Our specimens are smaller than those reported for the type species, but our scale dimensions were similar (Eikrem 1996, Puigserver et al 2003.…”
Section: Chrysochromulina Throndsenii Eikrem (Figures 4 31 32)mentioning
confidence: 41%
See 1 more Smart Citation
“…The center of the scales has a cruciform structure surrounded by an open ring with radiate ribs extending out of the central ring to the rim and crossed by spiraling ribs. Our specimens are smaller than those reported for the type species, but our scale dimensions were similar (Eikrem 1996, Puigserver et al 2003.…”
Section: Chrysochromulina Throndsenii Eikrem (Figures 4 31 32)mentioning
confidence: 41%
“…The preponderance of haptophytes in oligotrophic waters may be explained by their small cell size and ability to feed phagotrophically (Jones et al 1993, Hansen and Hjorth 2002, Lessard et al 2005, or, in the case of the genus Phaeocystis Lagerheim, by its ability to form gel-like colonies (Schoemann et al 2005). Many haptophyte species have been reported from a wide latitudinal range and, therefore, may be regarded as cosmopolitan (Estep et al 1984, Birkhead and Pienaar 1995a, Jensen 1998, Eikrem and Edvardsen 1999, Eikrem and Throndsen 1999, Puigserver et al 2003, LeRoi and Hallegraeff 2004, Hu et al 2005, Nakayama et al 2005.…”
Section: Introductionmentioning
confidence: 96%
“…Haptophytes in the Mediterranean Sea are represented by different species, mostly belonging to the genus Phaeocystis, Prymnesium and Chrysochromulina (for example, Zingone et al, 1999;Puigserver et al, 2003;Vila and Masó, 2005). Although the probes we used were not specific enough to determine if species shifts occurred during the study period, some variations in the mean cell size of haptophytes were observed along the year: a higher proportion of cells 45 mm was observed in December and smaller cells were found at the end of winter.…”
Section: Pico-and Nanophytoplankton Compositionmentioning
confidence: 98%
“…Besides this species, haptophytes of the genera Chrysochromulina were found in concentrations of about 4 · 10 5 cells l )1 , being probably underestimated, thus contributing to a certain extent to the Chl a content of the water. More important appears to be the contribution of Chrysochromulina lanceolata, which is one of the largest species in the genus, with between 21 and 38 lm length (Puigserver et al, 2003). In this study, a peak of 3.2 · 10 5 cells l )1 was registered in August at the seaward end, when 0.1694 lg l )1 of 19¢hex were measured.…”
Section: Phytoplankton Assemblages At the Outer Estuarymentioning
confidence: 99%